2021
DOI: 10.5468/ogs.20316
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation for primary dysmenorrhea: a double-blind, randomized, placebo-controlled trial

Abstract: Objective: Primary dysmenorrhea is believed to be common and associated with reduced quality of life among menstruating women. Recent studies have shown a possible association between vitamin D deficiency and the severity of primary dysmenorrhea. The present study aimed to investigate the effect of vitamin D supplementation on pain and systemic symptoms in patients with primary dysmenorrhea.Methods: This double-blind, randomized, placebo-controlled trial was conducted on female students aged 18 to 32 years wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 33 publications
0
40
0
4
Order By: Relevance
“…Vitamin D is essential for metabolic homeostasis and physiological function [5]. It has also been proposed to lessen or prevent female reproductive disorders [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is essential for metabolic homeostasis and physiological function [5]. It has also been proposed to lessen or prevent female reproductive disorders [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Another randomized controlled trial found that participants received vitamin D experienced signi cant reduction in menstrual pain, and the consumed painrelief medications [4].…”
Section: Discussionmentioning
confidence: 99%
“…Increased local prostaglandins with a subsequent increased amplitude of uterine contractions, and endometrial ischemia is the most accepted theory of primary dysmenorrhea [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In women with primary dysmenorrhea without the diagnosis of endometriosis different dosages (single 300.000 IU dose 5 days before menstruation [ 40 , 41 ] or 50.000 IU/ weekly [ 42 , 43 ]) of vit D supplementation can reduce pain intensity. A significantly greater mean decrease in pain has been also observed in a systematic meta-analysis evaluating vit D supplementation in patients with different kinds of pain (musculosceletal pain, arthritis, dysmenorrhea, migraine) xxx (mean difference -0.57, 95% CI: -1.00 to -0.15, P = 0.007) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%